Determining the learning culture and leadership in learning organization: a case of the Selangor state public library/ Norliya Ahmad Kassim and Muhammad Faizal lylia Mohd Ghazali - Ahmad Kassim, Norliya; Mohd Ghazali, Muhammad Faizal lylia (Faculty of Information Management, Universiti Teknologi MARA, 2014)
The purpose of this study is to identify the perceptions on the level of learning organization's practice in terms of learning culture in the Selangor State Public Library {PPAS) and the level of sustaining the library's performance. A research survey method using questionnaire was distributed to 100 staff in the Selangor State Public Library of which the return rate was 80 {8%}. The results of the survey were analyzed using the Statistical Package for the Social Sciences (SPSS). The findings showed that staff have positive perception on the level of learning culture (mean=3.84) and leadership (mean=3.85}. The results show that there are differences regarding learning culture and leadership according to gender. There are differences regarding learning culture according work position. The finding will be useful in urging public libraries, especially those in the public sector to become better and sustaining the learning organization's performance by improving learning culture practice, optimizing management activities, and creating a formalized learning system within their organizations.